SIMULATION OF AIRCRAFT OSCILLATIONS WHILE RUNNING ON THE TRAY AND LAND WITH WINDWARE WARNING - Шифрин, Б. М. (Proceedings of National Aviation University (archive), 2021)
Modeling of elastic-frictional oscillations of the aircraft in the direction of its transverse axis when moving at high speed on the runway and nonlinear chassis removal of the chassis is considered. A method for determining the parameters of the limit cycles is proposed and with its help the question of the presence of self-oscillations at a finite and infinite ratio of the masses of the aircraft body and its supports is studied.